Digitalisasi Informasi Budidaya Jambu Kristal: Inovasi Website untuk Peningkatan Pengetahuan Petani di Desa Cikarawang - Dema Mariska; Ajeng Dwi Rahayu; Aura Nurkhalis; Rina Octavia Hasanah; Kenji Faiz Kusuma; Andi Razan Ramiro; Muhamad Mulya Azhar; Agief Julio Pratama; M. Iqbal Nurulhaq; Tri Budiarto; Widya Hasian Situmeang; Ratih Kemala Dewi; Restu Puji Mumpuni; Edi Wiraguna (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
Crystal guava farmers in Cikarawang Village, Bogor Regency, face challenges in accessing information related to proper cultivation techniques, from seedling to harvest. The lack of access to valid and easy-to-understand sources of information causes farmers to have difficulty in dealing with various cultivation problems, such as pests, diseases, and effective fertilization. In response to these problems, an innovation was developed in the form of a digital agricultural website containing a complete summary of material on crystal guava cultivation. This website is designed to be easily accessible to farmers and functions as a practical and efficient one-way information media. In addition, this website is also equipped with an online community feature through a discussion group connected to expert mentors in the field of crystal guava cultivation. This feature allows farmers to share experiences, discuss, and obtain direct guidance from experts. This innovation is expected to improve farmers' knowledge, skills, and independence in managing crystal guava cultivation sustainably.